Athletes have different dominant cognitive functions depending on type of sport - Yongtawee, A.; Park, J.; Kim, Y.; Woo, M. (International Journal of Sport and Exercise Psychology, 2022)
High-performing athletes possess the ability to read the game, which is known as the "sports brain." The purpose of this study was to investigate differences in athletes` cognitive functions across sports and to identify the dominant cognitive functions in each type of sport. We classified sports as interceptive, static, or strategic. A total of 120 individuals participated in this study, including 30 boxers (interceptive), 30 competitive shooters (static), 30 soccer players (strategic), and 30 non-athletes. To measure the executive function (inhibition and cognitive flexibility), spatial ability, and information processing speed of the participants, we administered the trail making test (TMT), mental rotation test (MRT), design fluency test (DFT), flanker task (FKT), and tests of simple reaction time (SRT) and choice reaction time (CRT) using an original computer program. We found differences in dominant cognitive functions across sport types. Athletes in interceptive sports demonstrated advanced visuospatial functioning and processing speed, while athletes in strategic sports showed superior executive function, including working memory and cognitive flexibility. Athletes in static sports demonstrated the fastest visuo-perceptual processing among all groups. This study`s findings provide an understanding of the cognitive characteristics of athletes in interceptive, strategic, and static sports, which can aid in the discovery and recruitment of athletes based on their cognitive skills.